2002
DOI: 10.1210/en.2002-220563
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hyaluronan Synthase 2 by Human Chorionic Gonadotropin in Mural Granulosa Cells of Equine Preovulatory Follicles

Abstract: In contrast to other species, the preovulatory rise in gonadotropins in mares causes a remarkable expansion of the entire granulosa cell layer in vivo, suggesting that hyaluronan (HA) synthesis may be regulated in mural granulosa cells in this species. The objectives of this study were to clone and characterize equine hyaluronan synthase 2 (HAS2) and investigate the regulation of its transcript and of HA synthesis in equine follicles during human chorionic gonadotropin (hCG)- induced ovulation. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Alignment of gDNA sequences surrounding the 5Ј terminus of AJ604570 for human, murine, and equine HAS2 loci illustrated the high similarity suggested previously (24). Fig.…”
Section: Figsupporting
confidence: 73%
See 1 more Smart Citation
“…Alignment of gDNA sequences surrounding the 5Ј terminus of AJ604570 for human, murine, and equine HAS2 loci illustrated the high similarity suggested previously (24). Fig.…”
Section: Figsupporting
confidence: 73%
“…DNA Sequence Alignment and Data Base Analysis-Alignments for the genomic sequences upstream of HAS2 from human (clone RP11-3G20, sequence AC104233), mouse (clone RP24 -147N23, sequence AC140799), rat (clone CH230 -228F12, sequence AC105559), and horse (AF508308) (24) were carried out using the ClustalW algorithm at the European Bioinformatics Institute (www.ebi.ac.uk/clustalw/index. html).…”
Section: Methodsmentioning
confidence: 99%
“…(63,64) Increased HA secretion may thus be a common mechanism used by inflammatory cytokines to arrest osteoblast differentiation. The promoter sequences of all three HASs contain several putative transcription factor binding sites, (65)(66)(67)(68) and functional studies have confirmed the role of some regulators. For example, the p50/p65 NF-B complex regulates HAS1 expression in human fetal lung myofibroblasts in response to TNF-␣(54), and STAT-and RAR-response elements control expression of HAS2 in human keratinocytes.…”
Section: Has2 and Ha As Mediators Of The Lif Effectmentioning
confidence: 73%
“…The thicker band migrated to the molecular weight of around 63 k, and the thinner band migrated more slowly. Since HAS2 consists of 552 amino acids (23), its molecular weight is presumed to be about 63 k (33). In MU-treated cells, the intensity of the HAS2 bands in the phosphorylated protein fraction was weakened ( Fig.…”
Section: Effect Of Mu and Tpa On The Synthesis Of Hyaluronan And The mentioning
confidence: 98%